A geographical information system based multi-criteria decision-making approach for location analysis and evaluation of urban photovoltaic charging station: A case study in Beijing. (1st February 2020) - Zhou, Jianli; Wu, Yunna; Wu, Chenghao; He, Feiyang; Zhang, Buyuan; Liu, Fangtong
Highlights: A model is proposed for location decision of photovoltaic charging station. The factors for location analysis and evaluation are determined. The fuzzy theory is used to improve collection and description of information. An empirical study is carried out to verify the practicability of the model. Evaluation criteria with different recession coefficients would change the results. Abstract: The integration of photovoltaic (PV) power generation system and electric vehicle (EV) charging station can effectively promote the local consumption of renewable energy and reduce the indirect carbon emissions of EV. This paper aims to provide a practical model for location decision of PV charging station (PVCS) which combines geographic information system (GIS) with multi-criteria decision making (MCDM) methods. To verify the feasibility and practicality, an empirical study was conducted in Beijing. First, seven suitable areas were selected preliminarily by suitability analysis of GIS. This stage focused on traffic flow and road distribution. Second, MCDM methods were used to further evaluation. At this stage, a comprehensive evaluation index system of natural, economic, technical and social criteria was established. Interval number, triangular fuzzy number and hesitant fuzzy linguistic term set were utilized to collect and describe evaluation information. Then, the subjective and objective weights of the criteria were calculated by best-worst method and mixed information entropy method, respectively. Finally, the TODIM (an acronym in Portuguese of interactive and MCDM) method was used to rank the alternatives. The ranking results illustrated that alternative sites A3 and A7 are outstanding. Moreover, dual sensitivity analysis and comparative analysis proved the stability and reliability of the model. Scenario analysis expanded the application scope of TODIM method, which also showed that it is necessary to express decision preferences by setting different recession coefficients. This study can provide support for the layout of PVCS in urban, and enrich the application fields of GIS and MCDM methods.